The association between adverse reactions and immune response against SARS-CoV-2 spike protein after vaccination with BNT162b2 among healthcare workers in a single healthcare system: a prospective observational cohort study. Issue 5 (30th November 2022) - Jubishi, Daisuke; Okamoto, Koh; Hamada, Kensuke; Ishii, Takashi; Hashimoto, Hideki; Shinohara, Takayuki; Yamashita, Marie; Wakimoto, Yuji; Otani, Amato; Hisasue, Naoko; Ikeda, Mahoko; Harada, Sohei; et al.
ABSTRACT: Adverse reactions after vaccination with COVID-19 mRNA vaccines are common; however, the association between adverse reactions and humoral responses is uncertain. To determine whether humoral immune responses after BNT162b2 vaccine administration were associated with local and systemic adverse reactions, we conducted a prospective observational cohort study in a single tertiary referral center. Healthcare workers who received the first dose of BNT162b2 vaccine were recruited. SARS-CoV-2 anti-spike IgG antibody titers were measured three weeks after the second dose and information about adverse reactions after vaccination was collected. Among the 887 participants, 641 (72.3%) were women. The median age was 38 (range, 22–74) years. All but one showed anti-spike IgG levels well above the cutoff, with a median level of 13, 600 arbitrary units/mL. Overall, 800 (92.2%) participants reported some reactions after the first dose and 822 (96.3%) after the second dose. Significantly more participants reported systemic reactions after the second dose than after the first dose (P < .01), and 625 (73.6%) reported that reactions were stronger after the second dose. Factors positively associated with elevation of anti-spike IgG levels were history of asthma (24% higher if present, P = .01) and stronger reactions after the second dose (19% higher if experienced, P = .02). The majority of participants showed good humoral responses and reported some adverse reactions after vaccination. Anti-spike IgG levels were significantly higher if adverse reactions after the second dose were stronger than those after the first dose. These findings may help inform current and future vaccine recipients.